Exosomes: Emerging implementation of nanotechnology for detecting and managing novel corona virus- SARS-CoV-2 - Akhilesh Dubey; Cynthia Lizzie Lobo; Ravi GS; Amitha Shetty; Srinivas Hebbar; Sally A. El-Zahaby (Elsevier, 2022)
The spread of SARS-CoV-2 as an emerging novel coronavirus disease (COVID-19) had progressed as a worldwide pandemic since the end of 2019. COVID-19 affects firstly lungs tissues which are known for their very slow regeneration. Afterwards, enormous cytokine stimulation occurs in the infected cells immediately after a lung infection which necessitates good management to save patients. Exosomes are extracellular vesicles of nanometric size released by reticulocytes on maturation and are known to mediate intercellular communications. The exosomal cargo serves as biomarkers in diagnosing various diseases; moreover, exosomes could be employed as nanocarriers in drug delivery systems. Exosomes look promising to combat the current pandemic since they contribute to the immune response against several viral pathogens. Many studies have proved the potential of using exosomes either as viral elements or host systems that acquire immune-stimulatory effects and could be used as a vaccine or drug delivery tool. It is essential to stop viral replication, prevent and reverse the massive storm of cytokine that worsens the infected patients' situations for the management of COVID-19. The main benefits of exosomes could be; no cells will be introduced, no chance of mutation, lack of immunogenicity and the damaged genetic material that could negatively affect the recipient is avoided. Additionally, it was found that exosomes are static with no ability for in vivo reproduction. The current review article discusses the possibilities of using exosomes for detecting novel coronavirus and summarizes state of the art concerning the clinical trials initiated for examining the use of COVID-19 specific T cells derived exosomes and mesenchymal stem cells derived exosomes in managing COVID-19.